PENYALURAN DANA BUMG GAMPONG MATANG TUNONG LAPANG DALAM MENINGKATKAN PENDAPATAN MASYARAKAT PERSPEKTIF MANAJEMEN KEUANGAN SYARIAH - Yoesrizal M. Yoesoef; Nina Tursina (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2021)
Abstract This study aims to see how the mechanism for distributing village-owned enterprises funds in the village of Matang Tunong, Lapang District, in increasing the economic income of the community and how the distribution of these funds in the perspective of Islamic financial management. The research method used is descriptive qualitative with field studies, and data collection is done through interviews and observations. The results showed that the distribution of village-owned enterprise funds in the village of Matang Tunong which was distributed to the community was carried out in groups and according to sources obtained said the contract used was a murabahah contract. In addition, many people who take the funds are used for pond land management. Second, the implementation of the distribution of village-owned enterprise funds in the village of Matang Tunong for now has not been going well according to sharia financial management, besides that they are charged with a percentage of financing where loan repayments will increase if taken for a long time, so they cannot focus on So, according to Islamic financial management, the business that is run to be effective is done by looking at quality resources, planning work, analyzing environmental conditions and also monitoring or controlling.